2014
DOI: 10.1152/ajpendo.00495.2013
|View full text |Cite
|
Sign up to set email alerts
|

AICAR-induced activation of AMPK negatively regulates myotube hypertrophy through the HSP72-mediated pathway in C2C12skeletal muscle cells

Abstract: induced activation of AMPK negatively regulates myotube hypertrophy through the HSP72-mediated pathway in C2C12 skeletal muscle cells. Am J Physiol Endocrinol Metab 306: E344 -E354, 2014. First published December 17, 2013; doi:10.1152/ajpendo.00495.2013.-5=-AMP-activated protein kinase (AMPK) plays an important role as a negative regulator of skeletal muscle mass. However, the precise mechanism of AMPK-mediated regulation of muscle mass is not fully clarified. Heat shock proteins (HSPs), stress-induced molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 43 publications
4
54
1
2
Order By: Relevance
“…6E), suggesting that AMPK does not modulate HSF1 expression in unloading-induced skeletal muscle atrophy. This is supported by previous data showing that pharmacological activation of AMPK did not affect HSF1 expression in skeletal muscle cells (13). Thus, we consider that AMPK-mediated regulation of HSP72 during hindlimb unloading is independent of HSF1.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…6E), suggesting that AMPK does not modulate HSF1 expression in unloading-induced skeletal muscle atrophy. This is supported by previous data showing that pharmacological activation of AMPK did not affect HSF1 expression in skeletal muscle cells (13). Thus, we consider that AMPK-mediated regulation of HSP72 during hindlimb unloading is independent of HSF1.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a molecular mechanism of the resistance to skeletal muscle atrophy by HSP72 seems to be that HSP72 directly prevents FoxO3a activation during unloading (65,66). We have also demonstrated previously that AMPK negatively regulates HSP72 expression in skeletal muscle cells and that HSP72 controls AMPK-mediated activation of the ubiquitin-proteasome system (13). Considering these findings, it is suggested that a high expression of HSP72 due to the suppression of AMPK activity is a possible mechanism that attenuates the unloading-induced activation of the protein degradation system partly through FoxO3a deactivation.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations